1997
DOI: 10.1038/sj.ijo.0800500
|View full text |Cite
|
Sign up to set email alerts
|

Brown fat thermogenesis in rats fed high-fat diets enriched with n-3 polyunsaturated fatty acids

Abstract: OBJECTIVE:To examine the possible involvement of an increase in diet-induced thermogenesis from brown adipose tissue (BAT) in the n-3 polyunsaturated fatty acids (n-3 PUFA) induced limitation of the development of white fat pads during high-fat feeding. DESIGN: Rats fed for four weeks on a low-fat/high-carbohydrate diet (C group) or high-fat diet without n-3 PUFA (REF group), with eicosapentaenoic acid (EPA group), with docosahexaenoic acid (DHA group) or with a mixture of these two fatty acids (MIX group). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 39 publications
5
58
0
5
Order By: Relevance
“…EPA also increased glucose consumption in brown fat, which would correlate with the report of a marked stimulation of brown adipose tissue (BAT) thermogenic activity by n-3 polyunsaturated fatty acids (Oudart et al, 1997).…”
Section: supporting
confidence: 64%
“…EPA also increased glucose consumption in brown fat, which would correlate with the report of a marked stimulation of brown adipose tissue (BAT) thermogenic activity by n-3 polyunsaturated fatty acids (Oudart et al, 1997).…”
Section: supporting
confidence: 64%
“…In the whole animal the effect was detected by the measurement by indirect calorimetry of postprandial energy expenditure, which is higher in rats fed on n-6 PUFA than in saturated or monounsaturated fatty acid-fed rats . n-3 PUFA are also potent stimulators of diet-induced thermogenesis, as was clearly shown in BAT from rats fed on a diet enriched with fish oil fatty acids, which had a higher BAT thermogenic activity (Oudart et al 1997) and a higher UCP1 content (Sadurkis et al 1995;Kawada et al 1998) than rats fed on a lard-based diet. The results of all these studies are in accordance with a role for BAT thermogenesis in the limiting effect of PUFA on body fat accumulation.…”
Section: Effect Of Polyunsaturated Fatty Acids On Lipid Homeostasismentioning
confidence: 97%
“…A selective energy-dissipative process to counteract body fat accretion during high-fat feeding has been demonstrated (Rothwell & Stock, 1979), and may be implicated in the regulation of energy balance during high-fat feeding according to the fatty acid composition of dietary fat (Trayhurn, 1986). It has been shown that PUFA lead to a higher increase in diet-induced thermogenesis than saturated or monounsaturated fatty acids during high-fat feeding, suggesting that dietary fatty acids could be selectively thermogenic Oudart et al 1997). Diet-induced thermogenesis is brought about mainly by BAT, which is under the control of the sympathetic nervous system, through the activity of the uncoupling protein (UCP) 1. n-6 PUFA are more potent stimulators of the BAT sympathetic nervous system than saturated or monounsaturated fatty acids, as has been assessed by the higher BAT noradrenaline turnover in rats fed on n-6 PUFA than that in saturated or monounsaturated fatty acid-fed rats (Young & Walgren, 1994;Matsuo et al 1995).…”
Section: Effect Of Polyunsaturated Fatty Acids On Lipid Homeostasismentioning
confidence: 99%
“…La spécificité de l'effet biologique des acides gras alimentaires d'huile de poisson a été clairement montrée en utilisant des proportions similaires d'AGPI n-3, d'AGPI n-6, et d'acides gras saturés et mono-insaturés dans l'alimentation entre les différents groupes expérimentaux [7,15]. Ainsi, les effets des acides gras d'huile de poisson peuvent être attribués sans équivoque aux AGPI n-3.…”
Section: Effet Des Acides Gras Polyinsaturés Sur L'accumulation De Grunclassified
“…Dans une étude récente, des rats ont été nourris pendant 4 semaines avec quatre régimes riches en graisses différant par leur composition en acide gras mais contenant la même proportion d'AGPI n-3 (20:5n-3, groupe EPA ; 22:6n-3, groupe DHA ; 20:5n-3 plus 22:6n-3, groupe MIX), ou pas d'AGPI n-3 (groupe C). En parfait accord avec les études antérieures rapportées précédemment, la consommation d'AGPI n-3 influence le développement du tissu adipeux [15,16]. À l'issue du traitement nutritionnel, la masse de lipides et la taille des cellules adipeuses diminuent dans le tissu adipeux rétropéritonéal dans l'ordre suivant : groupe C > groupe EPA > groupe DHA > groupe MIX, mais restent inchangées dans le tissu adipeux sous-cutané (figure 2).…”
Section: Effet Des Acides Gras Polyinsaturés Sur L'accumulation De Grunclassified